Produção de celulose bacteriana em meio à base de melaço de soja em cultivo estático - Chagas, Bruna Santana das (2018)
Bacterial cellulose ( BC ) is a biopolymer that presents applications in the biomedical area , food, cosmetic, among others. However, its large - scale production is limited by, among some reasons, the cost of the process where the medium is responsible for up to 30% of the total cost of production. In t his c ontext, the soybean molasses (SM ), a co - product of low cost soybean, may be a promising substrate for the production of BC bec ause it contains carbon and nitrogen sources for the fermentation process . The objective of the work was to produce bacterial cellulose by Komagataeibacter xylinus ATCC 53582 in static culture, using soybean molasses as an alternative fermentation medium. To increase the content fer mentable sugar , the S M was hydrolyzed with sulfuric acid. Thus, assays were performed varying the acid and SM ratio and, later, an experimental design to optimize the hydrolysis of the oligosaccharides. From the results of the tests the hydrolysed fermenta tion media were formulated HSM75 (75 g/L aqueous solution of SM hydrolyzed with 5% (v/v) H 2 SO 4 1M) and HSM100 (100 g/L aqueous solution of SM hydrolyzed with 10% (v/v) H 2 SO 4 1M) heat - treated at 90 °C/ 10 min and , thereafter, pH adjusted to 6 , 0. Control solu tions were also prepared in which no acid was added, named MS75 and MS1 00, aqueous solutions with 75 g/L and 100 g/ L of SM , respectiv ely. For fermentation, the medium based on SM and HS (reference medium) with (1.0, 1.5 and 2.0% v / v) and without additio n of ethanol w ere inoculated with 10% (v/ v) culture of Komagataeibacter xylinus and incubated at 30 °C/ 1 0 days . Medium based on hydrolyzed SM showed higher BC pr oduction than unhydrolyzed medium due to the higher concentration of fermentable sugars present in the culture medium. However, the production of the biopolymer in HSM 75 and HSM 100 medium was lower than the reference HS medium, indicating the need for s upplementation to increase its production . Ethanol supplementation m ay increase the production of BC because the bacterium oxidizes ethanol to acetic acid, which through the Krebs cycle synthesizes ATP influencing the metabolic pathway to produce the biopolymer. The best biopolymer production was observed in the HSM 75 medium supplemented with 2,0% (v/ v ) ethanol ( HSM75 +), presenting a prod uction of CB (approximately 7 g/ L) similar to the HS medium. The BC obtained from HSM75 + medium was characterized and showed a chemical composition of BC standard, beginning thermal decomposition at around 312 ºC, cryst allinity index of 80%, morphology of the nanofibrils with typical characteristics of BC and good mechanical properties. The results found were similar to the cellulose produced in HS medium indicating that the composition of the SM medium did not significa ntly affect the properties of the biopolymer. In addition, on laboratory scale , the HSM75 + medium presented a lower cost in its elaboration (76%) when compared to HS medium. Therefore, the soybean molasses medium hydrolyzed and supplemented with ethanol ha s potential as a fermentation medium for CB synthesis